2020
DOI: 10.1038/s41575-019-0258-z
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota-derived metabolites as key actors in inflammatory bowel disease

Abstract: A key role of the gut microbiota in the establishment and maintenance of health, as well as in the pathogenesis of disease, has been identified over the past two decades. One of the primary modes by which the gut microbiota interacts with the host is by means of metabolites, which are small molecules that are produced as intermediate or end products of microbial metabolism. These metabolites can derive from bacterial metabolism of dietary substrates, modification of host molecules, such as bile acids, or direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
822
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,119 publications
(942 citation statements)
references
References 181 publications
(248 reference statements)
14
822
1
6
Order By: Relevance
“…Significant variations between the control group and the low EA treated group were identified, and Oxidative phosphorylation, Lipopolysaccharide biosynthesis, Arginine and proline metabolism, Folate biosynthesis and Biotin metabolism were more abundant in the low EA treated group. These metabolic changes are coincident with studies that reported beneficial impacts of dietary fiber intervention in IBD 3,34 . These results may indicate that EA could shift the composition and metabolic functions of colonic microbiota to restore microbial dysbiosis.…”
Section: Ethanolamine Promoted Tlr4/myd88 Dependent Signaling In Inflsupporting
confidence: 81%
See 3 more Smart Citations
“…Significant variations between the control group and the low EA treated group were identified, and Oxidative phosphorylation, Lipopolysaccharide biosynthesis, Arginine and proline metabolism, Folate biosynthesis and Biotin metabolism were more abundant in the low EA treated group. These metabolic changes are coincident with studies that reported beneficial impacts of dietary fiber intervention in IBD 3,34 . These results may indicate that EA could shift the composition and metabolic functions of colonic microbiota to restore microbial dysbiosis.…”
Section: Ethanolamine Promoted Tlr4/myd88 Dependent Signaling In Inflsupporting
confidence: 81%
“…Nutrient signals, microbiome dysbiosis, and host immunoreactions have a pivotal role in the development of inflammatory bowel diseases (IBD) and colorectal cancer [1][2][3][4] . The gastrointestinal tract not only acts as the primary site of food digestion and nutrition absorption but also provides an essential interface for the interactions of gut microbiota and immune systems 5 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, advances in next-generation sequencing (NGS) have revolutionized the analysis of complex microbial ecosystems including the gut microbiota, leading to advanced understanding of its role in health and disease [1][2][3][4][5][6]. Alterations in the composition and diversity of the gut microbiota communities have been correlated with a large number of diseases, such as in ammatory bowel disease [7][8][9][10][11], irritable bowel syndrome [12,13], metabolic disorders (e.g, type 2 diabetes (T2D), obesity and nonalcoholic fatty liver disease (NALFD)) [14][15][16][17][18][19], and more recently, cancer [20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%